Decoding and reading comprehension in Turkish :|a comparison of Turkish monolingual and Kurdish-Turkish bilingual children - Kurt, Serhat. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
This study investigated the longitudinal contributions of phonological awareness (PA), rapid automatized naming (RAN), phonological memory (PM), listening comprehension (LC) and vocabulary to Turkish decoding and reading comprehension among Turkish monolinguals (N=46) and Kurdish-Turkish bilinguals (N=50). In addition, it explored whether there was any performance difference between monolinguals and bilinguals in the development of these cognitive and linguistic components from kindergarten to Grade 1. The participants were individually tested at three times: at the beginning, at the end of the kindergarten, and at the end of Grade 1. The findings revealed a developmental pattern in PA, RAN, PM, LC and vocabulary performances across the groups from kindergarten to Grade 1. Separate mixed ANOVAs were conducted for each component to observe any performance differences among monolingual and bilingual children across the times. The monolinguals outperformed the bilinguals in all tests except for PA tests. That is, the bilingual children scored better on PA tests than their monolingual counterparts at the beginning of the kindergarten. However, this performance difference was faded in the later times, especially at Grade 1. On the other hand, monolinguals statistically did better than bilinguals especially in LC and vocabulary tests. The resuls of hierarchical regression analyses revealed that PA and RAN were significant predictors of decoding. As to reading comprehension, LC and vocabulary appeared to be the best predictors of reading comprehension. Similarly, decoding significantly contributed to reading comprehension.
Keywords: Grammar, Comparative and general Phonology.; Bilingualism in children -- Turkey.; Bilingualism in children -- Case studies.; Code switching (Linguistics) -- Case studies.; Turkish language.; Kurdish language.